Does intake of bread supplemented with wheat germ have a preventive role on cardiovascular disease risk markers in healthy volunteers? A randomised, controlled, crossover trial - Moreira-Rosário, André (2019)
Objective Intake of whole grains is associated with a reduced risk of cardiovascular disease (CVD). This evidence is also strong for bran alone, but findings about germ are conflicting. Our aim was to elucidate the role of germ in primary prevention of cardiovascular events, and therefore, a staple food was selected for 6 g of germ supplementation. This corresponds to sixfold increase in the global mean consumption of germ, while preserving the sensory proprieties of refined bread which is crucial for consumer's acceptance. Design Randomised, double-blinded, crossover, controlled clinical trial with 15-week follow-up comprising a 2-week run-in, two intervention periods of 4 weeks each and a 5-week washout period. Setting A single centre in the north of Portugal. Participants 55 eligible healthy adults (mean age of 34 years and body mass index between 19 and 38 kg/m2) were randomly assigned. Interventions The study consisted of two intervention periods including daily intake of refined wheat bread enriched with 6 g of wheat germ and control (non-enriched bread). Outcomes Changes in fasting cholesterol and triglycerides, fasting and postprandial glucose, insulin sensitivity and C reactive protein. Results We observed no significant effect of daily intake of wheat germ on cholesterol and triglycerides levels, on postprandial glucose response and on insulin sensitivity. Incremental area under curve glucose and homeostasis model assessment for insulin resistance did not change, suggesting that 6 g of wheat germ have no effect on glucose metabolism. No effect was also observed in the subgroup of participants who complied with the protocol (n=47). Conclusions The absence of alterations on lipid and glucose profiles suggests that germ up to 6 g/day may have no preventive effect on CVD risk. However, it is important to investigate other food vehicles that can accommodate higher doses of wheat germ in future studies.